Frequency of peripheral arterial disease and venous insufficiency in toenail onychomycosis - OZKAN, Fuat; OZTURK, Perihan; OZYURT, Kemal; İNCİ, Mehmet F.; KALENDER, Ali M.; BAKAN, Betul; YUKSEL, Murvet (Journal of dermatology, 2013)
ABSTRACT Onychomycosis in toenails is a common fungal infection and vascular abnormalities of lower extremities have been thought as one of the predisposing conditions. The aim of this study was to evaluate predisposition effect of venous insufficiency and peripheral arterial disease on toenail onychomycosis. Thirty‐three patients with bilateral onychomycosis in toenails and 37 control subjects, who had healthy nails, were enrolled in the study. Veins and arteries of lower extremities were examined with Doppler ultrasound in terms of venous insufficiency or peripheral arterial disease. Patients with onychomycosis presented more frequent venous insufficiency than the control group (42.4% and 10.8%, respectively; P = 0.003). Although all patients had bilateral onychomycosis, reflux was bilateral in six out of 14 patients with onychomycosis (42.8%). No significant difference in frequency of peripheral arterial disease was found in patients, compared to healthy controls. Our study demonstrated a significant relationship between onychomycosis and venous insufficiency, but not with peripheral arterial disease. Also, we point out discordance with bilateral onychomycosis and unilateral venous insufficiency.